การรับรู้รายการและการวัดมูลค่าตามมาตรฐานการบัญชีระหว่างประเทศ (IAS) ฉบับที่ 41 การบัญชีสำหรับการเกษตร : ความเหมาะสมในการนำมาใช้สำหรับธุรกิจสวนปาล์มน้ำมันในประเทศไทย - กุลวดี ลิ่มอุสันโน (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To study accounting practice concerning the recognition, measurement and recognition of change in value of biological assets and agricultural products of oil palm farm business in Thailand. In addition, this study survey the opinions of accountants of oil palm farm business, auditors, and academics on the suitability and the problems that may arise from using International Accounting Standard (IAS) No.41 "The accounting for agricultural" in oil palm farm business in Thailand. This study also analyzes the effects of using IAS No.41 on the financial statements and the analysis of financial statements in oil palm farm business in Thailand. This study uses the questionnaires to collect data from the accountants of oil palm farm businesses, auditors and academics, including depth interview with accounting managers of oil palm farm businesses. The study found that most oil palm farm businesses in Thailand recognize and measure the biological assets (oil palm trees) and agricultural products (oil palm seeds and oil palm) in terms of their cost. The change in value of biological assets are recognized as expense for the amortization of accumulative cost and the impairment loss. The change in value of agricultural products are recognized when net realizable value (NRV) is lower than cost. Furthermore, according to the opinions of most accountants of oil palm farm business in Thailand, using IAS No.41 in the said business is appropriate. However, most of the auditors and academics are not sure about it. The comparative analysis of the effects on financial statements from the application of IAS No.41 and Thai Accounting Standard (TAS) No.32 "Property plant, and equipment" reveals that the income from operations, assets and profitability ratios according to IAS No.41 are higher. On the other hands, cash flows from investment in the statement of cash flows, liquidity ratios and leverage ratios according to IAS No.41 are lower.